EFEKTIFITAS TERAPI EXPRESSIVE WRITING DENGAN TERAPI TERTAWA UNTUK MENURUNKAN STRESS PADA MAHASISWA TINGKAT AKHIR: THE EFFECTIVENESS OF EXPRESSIVE WRITING THERAPY WITH LAUGHTER THERAPY TO REDUCE STRESS IN FINAL LEVEL STUDENTS - Tuti Anggarawati; Diana Tri Lestari; Elisa Wahyu Ananda; Dina Selviana (JURNAL KEPERAWATAN SISTHANA, 2021)
Students are students who hold the highest educational status. The demands of students to complete assignments on time are very high, especially for final year students. Final year students have the obligation to make a final project because it is one of the graduation requirements. The task can be a stressor for students so that students become stressed. This situation, if not handled immediately by students, will result in anxiety and depression, suicidal ideation, poor lifestyle, disturbed sleep patterns, headaches, and feelings of helplessness. Students can face and complete the final project well if students are able to handle stress well. There are several techniques to reduce stress, namely expressive wraiting and laughing. This research was carried out quantitatively using a two-group pre-post test design method. The sample in this study was final year students totaling